Chemical Compositions and Antibacterial Effect of Essential Oil of Key Lime Leaves (Citrus aurantifolia Swingle: Rutaceae) - Jamal, Yuliasri; Pariwidjayanti, Aris Medta; Agusta, Andria (BRIN, 2012)
Steam distillation of essential oil from fresh key leaves of Key lime (Citrus aurantifolia Swingle) gave 0.4% yellow essential oil with distinctive fragrance. Five out of 40 components of the essential oil were identified as the major components with content above 5%, they were geranial (103%). limonene (10.2%), neral (8.94%), caryphyllene (5.72%), and citronellal (5.41%). The essential oil was active against four bacterial test, Bacillus subtilis NBRC 3134, Staphylococcus aureus NBRC 14276, Micrococcus luteus NBRC 14218, and Escherichia coli NBRC 14237. B. subtilis was the most sensitive bacterium with the widest inhibition area at 50% concentration of essential oil. Minimum Inhibition Concentration (MIC) value of essential oil against B. subtilis was 0.125%.